2019
DOI: 10.1097/apo.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Scleral Reinforcement to Prevent Progression of High Myopia

Abstract: Background:Myopia has become a global public health problem. High myopia is linked to pathologic myopia (PM). As the severity of myopia increases, excessive axial elongation of the globe exerts a biomechanical stretch on the posterior pole, followed by a series of retinopathy which can lead to marked visual impairment. Posterior scleral reinforcement (PSR) is the only way that may have the potential to prevent the progression of axial elongation. Some scholars expressed satisfaction with the efficacy and safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
1
26
0
3
Order By: Relevance
“…The SCP is located near the large retinal vessels in the RNFL; hence, its density might be less sensitive to alterations associated with axial elongation and thinning of the retina in high myopia. [41][42][43][44] Our findings indicated that the deep retina is more vulnerable to microvascular changes over time than the SCP in POAG eyes with high myopia. These findings remained significant after exclusion of all POAG eyes that developed VF deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…The SCP is located near the large retinal vessels in the RNFL; hence, its density might be less sensitive to alterations associated with axial elongation and thinning of the retina in high myopia. [41][42][43][44] Our findings indicated that the deep retina is more vulnerable to microvascular changes over time than the SCP in POAG eyes with high myopia. These findings remained significant after exclusion of all POAG eyes that developed VF deterioration.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Although existing strategies primarily revolve around preventing or retarding the onset and progression of myopia, there are also effective interventions for PS (macular buckling) and MTM (pars plana vitrectomy). 24 , 51 , 52 Treatment for PS and MTM are generally reserved for later stages where there is a foveal detachment or full-thickness macular hole necessitating urgent intervention to avoid permanent vision loss. 53 , 54 By establishing a possible association between PS/MTM and MMD, this may imply that early detection and early treatment of PS/MTM, prior to the current late-stage indications, may potentially prevent MMD development or progression.…”
Section: Discussionmentioning
confidence: 99%
“…L'étude LAMP (low-concentration atropine for myopia progression) [17] est le premier essai randomisé en double aveugle (contre placebo), utilisant l'atropine à faible concentration, permettant de fournir des preuves solides pour étayer son rôle dans le contrôle de la myopie. Il a résolu la controverse sur le dosage de l'atropine en démontrant une réponse dépendante de la concentration d'atropine (0,05 %, 0,025 % et 0,01 %) dans le Depuis, la technique a été modifiée dans les années 1970, mais elle reste assez invasive [19].…”
Section: Lentilles De Contact Défocalisantesunclassified